Measuring housing affordability: Scoping the real cost of housing - Crowe, Adam; Rowley, Steven (Australian Housing and Urban Research Institute, 2024)
Lower-income households make trade-offs to afford their housing costs but most of these are not accounted for in the housing affordability measurements used by policy makers, according to new AHURI research. As a result, housing can appear affordable even though it is of such poor quality it affects people’s health, it is too expensive to heat or cool or it is located far from employment opportunities so that householders have very high commuting costs.